2017
DOI: 10.21276/apalm.1558
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pulse Co-oximeter in Hemoglobin Estimation: A non invasive method

Abstract: Background: Total Hemoglobin(Hb) measurement is one of the most common and important parameter that is investigated in the laboratory. This non invasive method allows pain free continuous online patient monitoring with minimum risk of infection and facilitates real time data monitoring allowing immediate clinical reaction to the measured data. The objective of the study is to test the efficacy of pulse co-oximeter .Methods: Present study is a prospective comparative study. A total of 261 patients enrolled for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…SpHb method reported accurate Hb measurements and keeps track of continuous monitoring of bleeding in patients and also helped in the detection of anemia (18) . Many researchers demonstrated decreased accuracy during blood loss and also detect a decrease in Hb level in dynamic situations and also indicate the appropriate timing for further Hb measurements (19)(20)(21)(22)(23) . Several studies have shown that the need for blood transfusions can be significantly reduced during surgery with the help of constant monitoring of the hemoglobin level (24)(25)(26)(27) .…”
Section: Introductionmentioning
confidence: 99%
“…SpHb method reported accurate Hb measurements and keeps track of continuous monitoring of bleeding in patients and also helped in the detection of anemia (18) . Many researchers demonstrated decreased accuracy during blood loss and also detect a decrease in Hb level in dynamic situations and also indicate the appropriate timing for further Hb measurements (19)(20)(21)(22)(23) . Several studies have shown that the need for blood transfusions can be significantly reduced during surgery with the help of constant monitoring of the hemoglobin level (24)(25)(26)(27) .…”
Section: Introductionmentioning
confidence: 99%